2013
DOI: 10.1002/ps.3667
|View full text |Cite
|
Sign up to set email alerts
|

Single and fused transgenic Bacillus thuringiensis rice alter the species‐specific responses of non‐target planthoppers to elevated carbon dioxide and temperature

Abstract: Different types of transgenic Bt rice alter the species-specific responses of non-target planthoppers to elevated CO2 and temperature. Compared with their non-transgenic parental lines, the single transgenic Bt rice shows better performance in controlling the non-target planthopper S. furcifera by comparison with the fused transgenic Bt rice under elevated CO2 and temperature. It is suggested that multitypes of transgenic Bt rice be used in the field simultaneously in order to take advantage of high transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…There is an emerging consensus that elevated CO 2 and T levels are stimulatory (positive) and inhibitory (negative), respectively (Peters, ). First, this projected atmospheric warming, combined with projected atmospheric CO 2 level increases, may have marked ecological effects on the vegetative growth responses of agricultural plants, As elevated CO 2 and T also alter plant quality (nutritional and defensive characteristics) and quantity, and these effects may, in turn, be transmitted through food chains to higher trophic levels, such as insect herbivores (Newman, ; Stiling et al., ; Wan et al., ). Elevated CO 2 likely change the interspecific interactions among insect herbivores (Chen, Ge, & Su, ; Chen, Wu, Parajulee, & Ge, ; Gonzáles, Fuentes‐Contreras, & Niemeyer, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is an emerging consensus that elevated CO 2 and T levels are stimulatory (positive) and inhibitory (negative), respectively (Peters, ). First, this projected atmospheric warming, combined with projected atmospheric CO 2 level increases, may have marked ecological effects on the vegetative growth responses of agricultural plants, As elevated CO 2 and T also alter plant quality (nutritional and defensive characteristics) and quantity, and these effects may, in turn, be transmitted through food chains to higher trophic levels, such as insect herbivores (Newman, ; Stiling et al., ; Wan et al., ). Elevated CO 2 likely change the interspecific interactions among insect herbivores (Chen, Ge, & Su, ; Chen, Wu, Parajulee, & Ge, ; Gonzáles, Fuentes‐Contreras, & Niemeyer, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aphid responses seem to be host and even genotype-specific, and can be linked to quantitative and qualitative changes in foliar amino acids (Johnson et al, 2014). Using the examples mentioned above, a similar species-specificity (including population size and feeding rates) was applied to other hemipteran insects such as planthoppers Nilaparvata lugens Stål, Laodelphax striatellus Fallen and Sogatella furcifera Horváth, which showed different abundance responses when raised on rice (Oryza sativa) under eCO 2 conditions (Wan et al, 2014).…”
Section: Indirect Effects Of Climate Change Mediated Through Changes mentioning
confidence: 99%
“…However, Chen et al found that Bt rice (cv., KMD expressing Cry1Ab ) delayed nymphal development, decreased female fecundity, and reduced population density of N. lugens [11]. Its close relative, the white-backed planthopper, Sogatella furcifera Horváth, on the other hand, thrived on Bt rice under elevated CO 2 [12]. To what extent Bt rice can control rice planthoppers is largely unclear.…”
Section: Introductionmentioning
confidence: 99%